2017
DOI: 10.1007/s00468-017-1618-3
|View full text |Cite
|
Sign up to set email alerts
|

An annually-resolved stem growth tool based on 3D laser scans and 2D tree-ring data

Abstract: ring-width measurements at any point within the modeled tree stem, which present great potential for complex growth analyses. Stem volume, estimated with a bole volume function, deviated between − 1.65 and 1.9% from our model for four out of five trees. For the fifth tree deviations of 13% were observed. The agreement between the function and our model demonstrates the robustness of the presented approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…We tested a selection of hypotheses based on theoretical assumptions of the intrinsic relationships between the morphology and physiology of the trees, and their functions in shaping the wood anatomy. Corollary to previous findings (Kankare, et al 2022, Lenz, et al 2012, Wagner, et al 2018, our results showed that the radial growth rates and therefore the age of wood can be quite reliably estimated based on the morphology of the tree stems and crowns, but LWP and RD were more challenging to connect with the morphological properties at an annual resolution. However, despite the weak explanatory powers in predicting LWP and RD, our analysis gave clues of significant relationships between tree morphology and wood anatomy and enabled logical interpretations of the background mechanisms.…”
Section: Analysis Of the Resultssupporting
confidence: 70%
“…We tested a selection of hypotheses based on theoretical assumptions of the intrinsic relationships between the morphology and physiology of the trees, and their functions in shaping the wood anatomy. Corollary to previous findings (Kankare, et al 2022, Lenz, et al 2012, Wagner, et al 2018, our results showed that the radial growth rates and therefore the age of wood can be quite reliably estimated based on the morphology of the tree stems and crowns, but LWP and RD were more challenging to connect with the morphological properties at an annual resolution. However, despite the weak explanatory powers in predicting LWP and RD, our analysis gave clues of significant relationships between tree morphology and wood anatomy and enabled logical interpretations of the background mechanisms.…”
Section: Analysis Of the Resultssupporting
confidence: 70%
“…Luterbacher et al, 2004), and expectation maximization approaches (Mann et al, 2007; Rutherford et al, 2005; Schneider, 2001). Advances in random forest reconstructions (Athey et al, 2019; Wagner et al, 2018), neural networks (Gholami et al, 2019; Woodhouse, 1999), and paleoclimate data assimilation (DA; Acevedo et al, 2017), to name a few, are also expanding the potential applications of tree-ring data. Over nearly a century of statistical and numerical pioneering, many early dendrochronological limitations have been overcome by a combination of increased computing power and decreased computational costs and the development of advanced programming languages for analyses of large data sets.…”
Section: Statistical and Numerical Frontiersmentioning
confidence: 99%
“…Thus, LiDAR has the potential to help find trees that are particularly sensitive to many specific environmental variables or to expand geomorphic investigations to deepen our understanding of how surficial processes are recorded in tree-ring records. For example, Lopez Saez et al (2011) used the high resolution of LiDAR to recognize and precisely delineate abandoned debris flow channels and Wagner et al (2018) combined ground-based LiDAR (or Terrestrial Laser Scanning (TLS)) to produce an annual volumetric analysis of tree growth, capturing tree volume and carbon storage in a given tree at a point in time. The same method has been used to preserve precise surface details of wood excavated from archaeological sites, including individual tool marks (Tegel et al, 2012).…”
Section: Tree Rings and Remote Sensingmentioning
confidence: 99%
“…Furthermore, in addition to the regular tree attributes measured in practical field inventories, more detailed tree attributes, such as the stem curve or taper curve (stem diameter as a function of height), which reveal the wood productivity and quality, can be derived from TLS with high degrees of accuracy [9]. Studies have explored the use of TLS at the plot level for assessing stem volume and biomass components [10][11][12][13] for individual tree reconstruction, including branches, twigs, and leaves [3,14,15], in order to improve the physiological understanding of tree growth [16]. Moreover, TLS has been used for determining the stem curve [17,18], which is not easily measurable using conventional tools.…”
Section: Introductionmentioning
confidence: 99%